Sociabilidades e cotidiano : a Praça da Alfândega em Porto Alegre - Reiher, Carla Betânia (2015)
This study is inserted in the context of analysis of social interaction processes in urban areas, from the perspective of sociology of daily lives and in large cities, where from then seeks to apprehend these processes and reveal the minutiae of the day-to -day of individual users of such spaces. This research has as an empirical object the Praça da Alfândega located in the historic center of Porto Alegre; in order to investigate and apprehend the everyday peculiarities of individuals that take the square as a space for social interactions. The social reality of large urban centers brings with it a variety of forms, different from each other, of social interactions, and the city, for its complexity, a great laboratory studies of society and daily life, as it is home to a multiplicity of worlds, a plurality of contents, that individual takes for himself and prepares them in interactions, in socialization processes and practiced sociability. It is argued in this paper initially the influence of the writings of Georg Simmel for urban studies and social relations that underlie from ephemeral social interactions processes to sociability. Make a presentation of the field of sociology of daily life, as a form of analysis that emphasizes the individual's subjective processes, how they interact with each other and with the social reality around them in their day-to-day, revealing then, from microsocial analysis the interactions that underlie this reality. In the second part of this paper we will deal with an analysis of the formation of the empirical object (Praça da Alfândega) and the socio-spatial transformations that happened in it. Later we enter the current empirical field and data analysis in an attempt to capture the daily life of the square, its social representations, social mapping and social interactions allocated in such urban space. The urban studies, regarding the social sciences contribute to the knowledge of the urban social reality. The growth of cities, reflecting the population growth that largely derived from the rural exodus, attracted by the industrial development, leads us to one facet of the possibilities of such transformations studies that underlie most of the time for socioeconomic analysis in the macro-structural level. But on the other hand, these changes allow us also to analyze the social processes in its micro category, revealing the dynamics that underlie the urban social reality, and therefore the socio-spatial transformations; the social relations of this urban man and the social interactions processes in which it is immersed, and that will reflect the dynamic and social practices in urban spaces.